Simulation and Comparison of THD for Cascaded H-Bridge Multilevel Inverters Fed Three Phase Induction Motor at Several Levels Using by Matlab/Simulink - مهجة حنان (Latakia University Journal -Engineering Sciences Series, 2021)
Multi-level inverter technology has emerged recently as a very important alternative in the area of high-power medium voltage energy control. Moreover the advantages like high quality power output, low switching losses, low electro-magnetic interference. This research presents some of cascaded multilevel inverters and analyzes its work and effect on the load voltage regulation when it is connected to three phase induction motor drive. The cascaded H-bridge, among those types CHBMLI offers enhanced output voltage waveform with lesser THD when increasing the levels of inverter. In addition to that the preferred output values are controlled by modulating the width of the pulses by Pulse Width Modulation (PWM) technique. The results reveal that the CHBMLI is more appropriate for induction motor drive. The proposed topology developed by using Matlab/simulink software.